2018
DOI: 10.1371/journal.pone.0201070
|View full text |Cite
|
Sign up to set email alerts
|

Rapid sample preparation with Lyse-It® for Listeria monocytogenes and Vibrio cholerae

Abstract: Sample preparation is a leading bottleneck in rapid detection of pathogenic bacteria. Here, we use Lyse-It® for bacterial cellular lysis, genomic DNA fragmentation, and protein release and degradation for both Listeria monocytogenes and Vibrio cholerae. The concept of Lyse-It® employs a conventional microwave and Lyse-It® slides for intensely focused microwave irradiation onto the sample. High microwave power and a <60 second irradiation time allow for rapid cellular lysis and subsequent intracellular componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Previously, it was shown that extracellular DNA was visible after making bacterial suspensions. [16] However, it was only until after days to a week that L . monocytogenes cells osmotically lyse and the genomic DNA began to degrade.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was shown that extracellular DNA was visible after making bacterial suspensions. [16] However, it was only until after days to a week that L . monocytogenes cells osmotically lyse and the genomic DNA began to degrade.…”
Section: Resultsmentioning
confidence: 99%
“…monocytogenes cells osmotically lyse and the genomic DNA began to degrade. [16] Following one month, the saver cards containing the sample were rehydrated with 1.25 mL DI water and mixed to aid in the release of bacterial cells. The mixed suspension was microwave irradiated with or without Lyse-It at 10%, 30%, or 50% power for 60 seconds.…”
Section: Resultsmentioning
confidence: 99%
“…This data is concurrent with previous data that shows that bacterial DNA is also fragmented in to various sizes under a wide variety of conditions. [1214] To aid in the fragment analysis, a mathematical weighted size () was calculated per trial as shown in Eqs 1→ 2, where n 0 is the first peak detected and n is the final peak reported from the Bioanalyzer data. For these equations, y i wa s the reported fragment size at peak n 0 ≤ i ≤ n , R i is the relative concentration reported for each fragment, and x i was the calculated weight factor where 1 = ∑ i x i .…”
Section: Methodsmentioning
confidence: 99%
“…Lyse-It has been reviewed in the literature as a highly efficient way to rapidly break open a wide variety of bacterial cells and subsequently fragment DNA and RNA and degrade proteins. [1014] Lyse-It is a technology that utilizes highly focused microwave that increases the electromagnetic energy and subsequently temperature to the sample. By using gold equilateral triangles and a standard microwave, microwave power and time can be adjusted for tunable cellular lysis, intracellular component release, DNA fragmentation, and protein degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation